Cerebro y lenguaje - González V., Rafael; Hornauer-Hughes, Andrea (Revista Hospital Clínico Universidad de Chile, 2014)
Language is the most important way of communication of the human being. It is a complex and dynamic conventional system of signs that can be oral or written. Language is a functional system that depends on the simultaneous work of different areas of the brain, both cortical and subcortical, that are located primarily in the left hemisphere. There are several variables that have an effect on the representation of language in the brain, such as laterality, sex, scholarship and age. The areas and tracts related to language can be grouped in two pathways, dorsal and ventral. The first is related to expression and the second to comprehension. Aphasia takesplace when areas and tracts of the brain related to language are damaged.